Treatment modalities and risk of adverse events associated with biologic therapy: A 10‐year observational review of the Australasian Psoriasis Registry. (4th September 2020) - Doolan, Brent J; Koye, Digsu; Ling, Joanna; Cains, Geoffrey D; Baker, Christopher; Foley, Peter; Dolianitis, Con
Abstract: Background: Psoriasis is a chronic inflammatory disease affecting 2–3% of the Australasian population. Therapeutic options include topical agents, phototherapy, systemic immunomodulators and biologic agents. Biologics present an acceptable short‐ and medium‐term safety profile, derived mainly from randomised controlled trials (RCTs) and, however, may not represent real‐world rates of adverse events (AEs). Methods: A retrospective, observational study of patients enrolled in The Australasian Psoriasis Registry from April 2008 to October 2018 was conducted. Data were collected from 104 sites in Australia and New Zealand. Patient characteristics, treatments and AE data were collected. AEs were classified by MedDRA System events. Results: 2094 patients were included (3765 patient‐treatments), comprising; 1110 phototherapy, 1280 systemic and 1375 biologic therapy patient‐treatments. Treatment arms were not mutually exclusive. The mean ± SD from date of diagnosis of psoriasis to commencement of biologic therapy was 8.9 ± 12.3 years. Methotrexate had the longest exposure time (3740.3 patient‐years), and ustekinumab had the longest median (95% CI) time on treatment, 4.3 years (2.2, 6.6). AE differences on biologic treatment were present between patients who would have been eligible or ineligible for RCTs. Approximately 29% of registry patients would have been excluded from clinical trials enrolment. Patients ineligible for RCTs had increased adjusted hazard ratios (95% CI) of: infections and infestations (2.3, 1.7–3.1; P < 0.001), cardiac (8.2, 3.5–25.6; P < 0.001), gastrointestinal (3.5, 1.52–8.0; P < 0.001), hepatobiliary (5.6 1.7–19.1; P < 0.001), psychiatric (4.7, 1.5–14.1; P = 0.006) and eye disorders (4.8 1.5–15.6; P = 0.008), compared to those eligible for RCTs. Incidence rates in the trial eligible patients were similar to those reported from RCT rates. Conclusions: This study establishes treatment modalities in use for severe psoriasis and the clinical rates of AEs associated with biologic therapy.